Fungal immunity and pathogenesis in mammals versus the invertebrate model organism Galleria mellonella - F. Q. Smith, Daniel; Casadevall, Arturo (Pathogens and disease, 2021)
ABSTRACT In recent decades, Galleria mellonella (Lepidoptera: Pyralidae) have emerged as a model system to explore experimental aspects of fungal pathogenesis. The benefits of the G. mellonella model include being faster, cheaper, higher throughput and easier compared with vertebrate models. Additionally, as invertebrates, their use is subject to fewer ethical and regulatory issues. However, for G. mellonella models to provide meaningful insight into fungal pathogenesis, the G. mellonella–fungal interactions must be comparable to mammalian–fungal interactions. Indeed, as discussed in the review, studies suggest that G. mellonella and mammalian immune systems share many similarities, and fungal virulence factors show conserved functions in both hosts. While the moth model has opened novel research areas, many comparisons are superficial and leave large gaps of knowledge that need to be addressed concerning specific mechanisms underlying G. mellonella–fungal interactions. Closing these gaps in understanding will strengthen G. mellonella as a model for fungal virulence in the upcoming years. In this review, we provide comprehensive comparisons between fungal pathogenesis in mammals and G. mellonella from immunological and virulence perspectives. When information on an antifungal immune component is unknown in G. mellonella, we include findings from other well-studied Lepidoptera. We hope that by outlining this information available in related species, we highlight areas of needed research and provide a framework for understanding G. mellonella immunity and fungal interactions. Galleria mellonella is a useful model for studying fungal infections with Galleria sharing many similarities with mammals' antifungal immune system and interactions with fungal virulence factors.